Penerapan Model DIR/Floortime dalam Meningkatkan Kemampuan Komunikasi Interaktif Anak dengan ADHD : Implementation of the DIR/Floortime Model to Enhance Interactive Communication Skills in Children with ADHD - Adila Rahmah Lathifah; Eka Sapti Cahya Ningrum (ITScience (Information Technology and Science), 2026)
This study aimed to analyze the interactive communication skills of a child with Attention Deficit Hyperactivity Disorder (ADHD) before and after the implementation of the Developmental, Individual Differences, Relationship-Based (DIR)/Floortime model, and to examine the model's effectiveness in enhancing these skills in a 5–6-year-old child in Group B at TK IT Daarussalaam. The interactive communication skills examined included initiating communication, responding to communication, maintaining eye contact, joint attention, and turn-taking. The study employed a quantitative approach using a Single Subject Research (SSR) experimental method with an A–B design. The subject was a 6-year-old boy diagnosed with ADHD, selected via purposive sampling. The study consisted of five sessions in the baseline phase (A) and ten sessions in the intervention phase (B) using the DIR/Floortime model. Data were collected through structured observation and analyzed using SSR visual analysis, covering trend direction, stability, level change, data range, and percentage of overlap. The results indicated that interactive communication skills during the baseline phase were low, with a score of 40%. Following the intervention, all indicators showed improvement, characterized by a greater ability to initiate and respond to communication spontaneously, as well as more consistent eye contact, joint attention, and turn-taking. Visual analysis revealed an increase in level, 90% data stability, and no overlap between phases. Thus, the DIR/Floortime model proved effective in enhancing the interactive communication skills of a 5–6-year-old child with ADHD.